The haunted bedroom: female sexual identity in Gothic literature, 1790-1820 - Rae, Angela Lynn (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1999)
This thesis explores the relationship between the Female Gothic novel of the late eighteenth and early nineteenth century and the social context of women at that time. In the examination of the primary works of Ann Radcliffe, Mary Wollstonecraft and Mary Shelley, this study investigates how these female writers work within the Gothic genre to explore issues related to the role of women in their society, in particular those concerned with sexual identity. It is contended that the Gothic genre provides these authors with the ideal vehicle through which to critique the patriarchal definition of the female, a definition which confines and marginalizes women, denying the female any sexual autonomy. The Introduction defines the scope of the thesis by delineating the differences between the Female Gothic and the Male Gothic. Arguing that the Female Gothic shuns the voyeuristic victimisation of women which characterizes much of the Male Gothic, it is contended that the Female Gothic is defined by its interest in, and exploration of, issues which concern the status of women in a patriarchy. It is asserted that it is this concern with female gender roles that connects the overtly radical work of Mary Wollstonecraft with the oblique critique evident in her contemporary, Ann Radcliffe's, novels. It is these concerns too, which haunt Mary Shelley's texts, published two decades later. Chapter One outlines the status of women in the patriarchal society of the late eighteenth century, a period marked by political and social upheaval. This period saw the increasing division of men and women into the "separate spheres" of the public and domestic worlds, and the consequent birth of the ideal of "Angel in the House" which became entrenched in the nineteenth century. The chapter examines how women writers were influenced by this social context and what effect it had on the presentation of female characters in their work, in particular in terms of their depiction of motherhood. Working from the premise that, in order to fully understand the portrayal of female sexuality in the texts, the depiction of the male must be examined, Chapter Two analyses the male characters in terms of their relationship to the heroines and/or the concept of the "feminine" . Although the male characters differ from text to text and author to author, it is argued that in their portrayal of "heroes and villains" the authors were providing a critique of the patriarchal system. While some of the texts depict male characters that challenge traditional stereotypes concerning masculinity, others outline the disastrous and sometimes fatal consequences for both men and women of the rigid gender divisions which disallow the male access to the emotional realm restricted by social prescriptions to the private, domestic world of the female. It is contended that, as such, all of the texts assert the necessity for male and female, masculine and feminine to be united on equal terms. Chapter Three interprets the heroine's journey through sublime landscapes and mysterious buildings as a journey from childhood innocence to sexual maturity, illustrating the intrinsic link that exists between the settings of Gothic novels and female sexuality. The chapter first examines the authors' use of the Burkean concept of the sublime and contends that the texts offer a significant revision of the concept. In contrast to Burke's overtly masculinist definition of the sublime, the texts assert that the female can and does have access to it, and that this access can be used to overcome patriarchal oppression. Secondly, an analysis of the image of the castle and related structures reveals that they can symbolise both the patriarchy and the feminine body. Contending that the heroine's experiences within these structures enable her to move from innocence to experience, it is asserted that the knowledge that she gains, during her journeys, of herself and of society allows her to assert her independence as a sexually adult woman.
Keywords: Wollstonecraft, Mary, 1759-1797 -- Criticism and interpretation; Shelley, Mary Wollstonecraft, 1797-1851 -- Criticism and interpretation; Gothic literature; Women and literature; Feminism and literature; Radcliffe, Ann Ward, 1764-1823 Criticism and interpretation